2022
DOI: 10.3390/ijerph19095426
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and Positive Orientation in Polish Adults with Multiple Sclerosis: The Role of Meaning in Life

Abstract: Scientific achievements concerning the direct relation between personality traits and positive orientation among patients with multiple sclerosis do not explain the role of potential mediators. In fact, some researchers argue that the traits–positivity association is much more complex than it seems to be. For this reason, we made an attempt to analyze the indirect relationship between the above-mentioned variables, including meaning in life as a mediator. In total, 618 patients with MS took part in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 119 publications
(149 reference statements)
1
2
0
Order By: Relevance
“…3,35 A recent review study reported that personality traits such as conscientiousness, agreeableness and extraversion were lower and neurotic personality traits were more dominant in MS patients. 14 Different studies have also reported that neuroticism is a dominant personality trait in MS patients 8,9 and this situation is similar to our current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3,35 A recent review study reported that personality traits such as conscientiousness, agreeableness and extraversion were lower and neurotic personality traits were more dominant in MS patients. 14 Different studies have also reported that neuroticism is a dominant personality trait in MS patients 8,9 and this situation is similar to our current study.…”
Section: Discussionsupporting
confidence: 92%
“…3,11,12 Conversely, positive personality traits such as extraversion, conscientiousness and openness have been reported to be protective factors against physical and neuropsychiatric symptoms. 13,14 In the light of these data, it can be said that personality traits affect the quality of life in a direct or indirect way. Although personality traits and quality of life have not been frequently studied in MS patients, some studies support this statement.…”
Section: Introductionmentioning
confidence: 99%
“…There is some empirical evidence that positive orientation correlates with openness to experience. 84,85 Such a result is not surprising if we think that openness to experience and openness to revising one's viewpoints likely share a common variance. However, there are also some studies that, like the current study, show an association between positive orientation and openness to experience at the level of tendency.…”
mentioning
confidence: 99%